Dynamic Response of Spar Platforms Subjected to Waves and Current - O. A. A., Montasir; Kurian, V.J.; Sambu Potty, Narayanan; B A Wahab, M. Mubarak (2008)

(untitled)
As the research for oil and other natural resources have progressed into deeper waters, the traditional fixed type of offshore structures have become unsuitable and new technologies had to be resorted to. Spar is a type of deepwater floating type of platform used in ultradeep waters of depth more than 1500 m. It is worth mentioning here that Malaysia has recently installed its first spar at Kikeh field near Sabah. In this study, dynamic analysis of two typical types of spar platforms such as classic spar and truss spar have been conducted and the motion responses in surge, heave and pitch have been evaluated. The spar platform has been modeled as a rigid body connected to the sea floor by multi-component catenary mooring lines. Unidirectional regular wave and random wave model spectra are used for computing the incident wave kinematics by Chakraborti’s Stretching Formula and for computing the wave force by modified Morison Equation. The response analysis has been performed in time domain to solve the dynamic behavior of the moored spar platform as an integrated system using the iterative incremental Newmark Beta approach. The results show that truss spar has better responses when subjected to waves and ambient deep current. Even though the truss spar responses are higher when subjected to waves, this spar is increasingly becoming popular because of lower cost.